One Health and the wildlife rehabilitator - Deem, Sharon L (Wildlife Rehabilitation Bulletin, 2024)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The One Health approach is gaining momentum as a transdisciplinary movement for finding solutions to the greatest challenges threatening the health of all life on Earth today. These threats range from climate change and emerging infectious diseases to pollution and the ever-expanding agricultural footprint. As awareness of the interconnection of the health of animals, humans, plants, and our shared environments has grown in recent years, so too has an appreciation for finding solutions to mitigate those challenges threatening our shared One Health. Within the One Health approach is the important role of the wildlife rehabilitator. As wildlife rehabilitators, we provide temporary care for diseased wildlife so that we may introduce them back into their appropriate habitats. The importance of healthy wildlife populations to ensure the health of domestic animals, humans, and the environments that support all life is central to our jobs as wildlife caregivers, and it is core to the One Health mission. Approaching our work through a One Health lens, we may create a healthier world for wildlife patients, the populations they represent, the habitats where they belong, and the domestic animals and humans that share their environments.